Two methods for modeling vibrations of planetary gearboxes including faults: Comparison and validation. (August 2017) - Parra, J.; Vicuña, Cristián Molina
Highlights: Models are used to study frequency content of planetary gearbox vibrations. Lumped-parameter model results decomposed into inertial reference frame. Local fault modeling: planet, sun and ring gear, in agreement with measurements. Increased difficulty in diagnosing single-tooth faults in ring gear. Existence of additional modulation for the local fault in the sun gear. Abstract: Planetary gearboxes are important components of many industrial applications. Vibration analysis can increase their lifetime and prevent expensive repair and safety concerns. However, an effective analysis is only possible if the vibration features of planetary gearboxes are properly understood. In this paper, models are used to study the frequency content of planetary gearbox vibrations under non-fault and different fault conditions. Two different models are considered: phenomenological model, which is an analytical-mathematical formulation based on observation, and lumped-parameter model, which is based on the solution of the equations of motion of the system. Results of both models are not directly comparable, because the phenomenological model provides the vibration on a fixed radial direction, such as the measurements of the vibration sensor mounted on the outer part of the ring gear. On the other hand, the lumped-parameter model provides the vibrations on the basis of a rotating reference frame fixed to the carrier. To overcome this situation, a function to decompose the lumped-parameter model solutions to a fixed reference frame is presented. Finally, comparisons of results from both model perspectives and experimental measurements are presented.